Law or jurisprudence? Considerations on determining the suspension period of the prescription of criminal prosecution - Pariona Arana, Raúl (2024)
The article addresses the problem of determining the suspension period of the prescription of criminal prosecution. It analyzes its legal regulation, its subsequent determination by Law 31751, and the impact of Plenary Agreement 05-2023/CIJ-112.After discussing the scope of the principle of legality, the separation of powers, and the constitutional review of criminal law, de lege lata, is defined that in our legal system, Law 31751 establishes the limit of the suspension period of the prescription. Finally, de lege ferenda, a legislative reform is proposed that does not assign suspensive effects to the act of formalizing the preparatory investigation and that the suspension period lasts as long as it takes to resolve the impeding cause.